Rethinking military command and control systems - George-Ion TOROI (Bulletin of "Carol I" National Defense University)
The evolution of society and the new characteristics of armed conflict, as demonstrated in today’s wars, highlight the need to adapt the military system to meet current and future challenges. In an increasingly complex and contested operational environment, command and control systems must be the first priority in this endeavour because of their impact on all other components of the military domain. Moreover, the technologization of society and the increased transparency of the confrontational environment place additional pressure on ensuring the effective protection and functionality of command-and-control systems. This article explores the need to rethink the architecture and fundamentals of C2 systems, analysing the essential elements that support operational effectiveness: flexibility, modularity, survivability, small footprint and resilience. In the context of new multi-domain operational paradigms and accelerated technological progress, C2 adaptation involves the integration of emerging technologies such as artificial intelligence, automation and real-time response capabilities to optimize decision-making. In particular, it emphasizes the importance of modularity and redundancy to ensure the operation of systems under conditions of intense conflict, as well as reducing electromagnetic vulnerability and increasing mobility. The article’s conclusions propose practical solutions for adapting C2 systems organized around the four components of people, processes, technology systems and command posts, highlighting their essential role in achieving decision advantage, a critical element of operational success on the modern battlefield.